Efficacy of Handheld Electronic Visual Supports to Enhance Vocabulary in Children With ASD. (March 2014) - Ganz, Jennifer B.; Boles, Margot B.; Goodwyn, Fara D.; Flores, Margaret M.
Although electronic tools such as handheld computers have become increasingly common throughout society, implementation of such tools to improve skills in individuals with intellectual and developmental disabilities has lagged in the professional literature. However, the use of visual scripts for individuals with disabilities, particularly those with autism spectrum disorders, has been demonstrated to be effective, though frequently in static formats. Thus, this study involved the implementation of an alternating-treatment design to investigate the effects of tablet computer-based visual scripts on vocabulary use in three 8- to 14-year-old children with autism. Results indicated that all the participants showed increased use of verbs or nouns with the treatment materials, all the participants required less invasive prompts as the project progressed, and one participant had mixed results in the spontaneous use of nouns, increasing in their use in treatment and nontreatment conditions.